Respuesta :

DeanR

1.1

x³ - 2x² -3 x = 0

x(x² - 2x - 3) = 0

x(x + 1)(x - 3) = 0

Answer: x = 0 or x=-1 or x=3

1.2

0= x³ - 4x = x(x² - 4) = x(x+2)(x-2)

Answer: x=0 or x=-2 or x=2

2.1

x⁴ - 2x³ + 3x² - 6x = 0

x(x³ - 2x² + 3x - 6) = 0

x(x²(x-2) + 3(x-2)) = 0

x(x² + 3)(x - 2) = 0

Answer: x=0 or x=2 or x= ±i√3

2.2

x⁵ - x⁴ - 2x³ +2 x² = 0

x²(x³ - x² - 2x + 2) = 0

x²( x²(x - 1) - 2(x - 1)) = 0

x²(x²-2)(x - 1) = 0

Answer: x=0 or x=1 or x= ±√2

3.1

x³ + 64 = 0

(x + 4)(x² - 4x + 16) = 0

x=-4 or x = 2 ±√(2²-16) = 2±2i√3

Answer: x=-4 or x = 2 ± 2i√3

3.2

x³ - 125 = 0

(x - 5)(x² + 5x + 25) = 0

quadratic x=(1/2)(-5 ±√(5²-4(25)) = (1/2)(-5 ± 5√3)

Answer: x=5 or x= (1/2)(-5 ± 5√3)

ACCESS MORE